The Role of International Court Justice (ICJ) in Resolving South China Sea Disputes Positivism Perspective - Nisa, Aulia Tiara; Diba, Intan Farah; Susilowati, Ida (Mediasi Journal of International Relations, 2024)
The Law of the Sea increasingly developed in the 19-20 centuries marked by the 1982 UNCLOS Convention on the Law of the Sea. This research discusses the role of UNCLOS in handling South China Sea disputes. And how is the settlement of the South China Sea dispute based on the International Court of Justice? This study uses qualitative methods based on secondary data sources derived from books, the internet, documents, journal articles, media, and others. The theory used in this study is one of the theories of positivism with an international law approach. The South China Sea dispute began with China's claims to the seas listed on its Nine Dashed Line map. Cases of disputes over the jurisdiction of the ICJ against the agreement of the disputing parties are to be submitted to the International Court of Justice. Cases submitted to the International Court of Justice contain the determination of the matters in question as well as various kinds of questions submitted to the International Court of Justice. If viewed from the perspective of positivism, the position of national law is higher than international law, so the claims of the South China Sea that have existed since the Han dynasty cannot be denied if China itself does not ratify international law and does not ratify UNCLOS and still adheres to the principles of national law or jurisdiction of its country. As the International Court of Justice, this dispute should be resolved by the jurisdiction of the International Court of Justice.